2009
DOI: 10.3143/geriatrics.46.541
|View full text |Cite
|
Sign up to set email alerts
|

Marked PT-INR prolongation associated with appetite loss due to urinary tract infection in a late elderly case with chronic atrial fibrillation

Abstract: An 80-year old woman presented with macroscopic hematuria on June 4(th), 2008. She had been suffering from general malaise and appetite loss since about 10 days previously. She had received anticoagulant therapy with warfarin due to chronic atrial fibrillation and PT-INR was well controlled between 1.6-2.2. When she presented, PT-INR was 12.88, and urinary tract infection (UTI) and hypoalbuminemia (2.2 g/dl) were observed. Therefore, warfarin therapy was discontinued, and antibiotics and vitamin K were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Since warfarin strongly binds to serum albumin [19], low levels of serum albumin increase the risk of INR prolongation [20,21]. A slight decline in albumin can also increase the INR value [18]. In our cases, serum albumin as well as A/G ratio was low, suggesting that hypoalbuminemia increased INR value.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Since warfarin strongly binds to serum albumin [19], low levels of serum albumin increase the risk of INR prolongation [20,21]. A slight decline in albumin can also increase the INR value [18]. In our cases, serum albumin as well as A/G ratio was low, suggesting that hypoalbuminemia increased INR value.…”
Section: Discussionmentioning
confidence: 53%
“…In the elderly, poor oral intakes of dietary vitamin K is the most likely explanation for the marked prolongation of INR despite a stable dose of warfarin [17]. We could not exclude the possibility that both cases were insufficient for taking vitamin K. On the other hand, hypoalbuminemia due to appetite loss exhibits a marked prolongation of INR [18]. Since warfarin strongly binds to serum albumin [19], low levels of serum albumin increase the risk of INR prolongation [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In practice, the importance of paying close attention to serum albumin levels during oral warfarin therapy has been indicated [6]. In a similar case, Saito et al [7] reported the case of an elderly patient with chronic atrial fibrillation who was on chronic warfarin therapy and who developed a urinary tract infection, which resulted in appetite reduction and hypoalbuminemia, which led to sudden PT-INR elongation. Fukuda et al [8] reported that the prevalence of malnutrition, defined as hypoalbuminea less than 3.4 g/dl, was 24.7% in Japanese patients with RA, and the characteristic progression of malnutrition was attributed to excessive protein catabolism evoked by inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 98%